'La iha fiar, la iha seguransa': the spiritual landscape and feeling secure in Timor-Leste. Issue 2 (4th May 2017) - Winch, Bronwyn
Abstract: While the spiritual landscape in Timor-Leste has been widely acknowledged and documented, its security dimensions remain relatively unexplored and under-theorised. This article argues that there are many different dimensions of security, and that a more holistic acknowledgement of the beliefs and practices which constitute a prominent basis for the ways that people engage with and understand the world is required. Building on qualitative fieldwork conducted in 2016, this article examines how, in Timor-Leste, engagement with the spiritual landscape informs to a significant extent how people experience, understand and produce security, in ways that state-based security provision often cannot.